The impact of sustainable marketing techniques adoption on the global marketing strategy in car dealers from district of Porto – Northern Portugal - Gomes, José Pedro Loureiro (2021)
Today’s consumer is better informed and has an enormous power to disseminate information. Sustainable Marketing emerges, in this context, as an innovative way to do marketing, creating an approach to new consumer demands. It involves long-term, sustainable strategies that truly add value to society, companies and the environment. The two main objectives of this study go through the analysis of Car Dealerships Sustainable Marketing Strategies and tries to identify the Sustainable Marketing-Mix adopted in the electrified vehicles (EV, PHEV and HEV) commercialization process. Therefore, the study seeks to understand if car dealerships in Porto district (Northern Portugal) incorporate a sustainable strategy consistent with the sustainable offerings that they have (EV, PHEV and HEV). The study is based on the adoption of a qualitative methodology with a non-probabilistic sample: a convenience sample. All the car dealerships involved in the investigation were selected based on the criteria of brand recognition as authorized dealers for their marketing and representation. All information collected from car dealerships was carried out through the technique of semi-structured interviews. The main conclusions found are that car dealerships, in different levels of involvement, have been introducing and developing sustainable practices and actions in their marketing strategies recognizing the importance of it. Due to the Marketing-Mix the car dealerships are very limited by the brands guidelines that they represent, however it’s in the promotion aspect that they invest the most and where they are increasingly differentiating and betting, understanding the importance recognized by their customers regarding the adoption of sustainable marketing strategies.